Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1136/bcr.09.2010.3319
|View full text |Cite
|
Sign up to set email alerts
|

Advanced, recurrent mesothelioma growth mimicking an aortic dissection

Abstract: In the emergency setting, a cold, clammy, dyspnoeic patient presenting with interscapular chest pain and unequal blood pressures suggests an acute aortic dissection until proven otherwise. By means of a case report, the authors detail one such patient who presented identically to one having an acute aortic dissection. Initial assessment showed unequal blood pressures in left and right arms, a resting tachycardia and indistinct heart sounds. Fluid resuscitation failed to improve the patient's physiological para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Although rare, complications of malignant pleural mesotheliomas have mimicked acute thoracic vascular pathology [4,5]. Retrospectively, the acute onset of chest pain in our patient was attributed to intratumour haemorrhage and the increased density of the periaortic fluid collection signified peritumour bleeding; this acute change resulted in hypotension.…”
Section: Discussionmentioning
confidence: 58%
“…Although rare, complications of malignant pleural mesotheliomas have mimicked acute thoracic vascular pathology [4,5]. Retrospectively, the acute onset of chest pain in our patient was attributed to intratumour haemorrhage and the increased density of the periaortic fluid collection signified peritumour bleeding; this acute change resulted in hypotension.…”
Section: Discussionmentioning
confidence: 58%
“…3,4 A review of the literature revealed that cases of thoracic mesothelioma mimicking ADA have been reported; however, few reports of lung cancer presenting with symptoms suggestive of ADA have been documented. 5,6 In our case, this tumor presented unique growth by surrounding the aorta and symptoms of intermittent chest pain, which resulted in a false preoperative diagnosis because of similar clinical characteristics to ADA.…”
Section: Discussionmentioning
confidence: 79%